Using the lamp instead of looking into the mirror : women and men in discussion about the relationship between men and women in the work place - Beinum, Ingrid Ljungberg van (Dialogues on work and innovation, 2000)
This book focuses on the enigmatic relationship between men and women, and in particular on the subordination of women by men in the work place. The main points of departure are that subordination is a relational phenomenon and should therefore be approached in a relational context and that the dynamics of relational behaviour primarily evolve through dialogue. The project facilitated and encouraged women and men to engage in more than 100 discussions about their daily relationships, carried out in the context of an intra- and inter-organizational action research project involving three organi.